mTORC2 Regulates Cardiac Response to Stress by Inhibiting MST1 - Sebastiano Sciarretta; Peiyong Zhai; Yasuhiro Maejima; Dominic P. Del Re; Narayani Nagarajan; Derek Yee; Tong Liu; Mark A. Magnuson; Massimo Volpe; Giacomo Frati; Hong Li; Junichi Sadoshima (Cell Reports, 2015)
The mTOR and Hippo pathways have recently emerged as the major signaling transduction cascades regulating organ size and cellular homeostasis. However, direct crosstalk between two pathways is yet to be determined. Here, we demonstrate that mTORC2 is a direct negative regulator of the MST1 kinase, a key component of the Hippo pathway. mTORC2 phosphorylates MST1 at serine 438 in the SARAH domain, thereby reducing its homodimerization and activity. We found that Rictor/mTORC2 preserves cardiac structure and function by restraining the activity of MST1 kinase. Cardiac-specific mTORC2 disruption through Rictor deletion leads to a marked activation of MST1 that, in turn, promotes cardiac dysfunction and dilation, impairing cardiac growth and adaptation in response to pressure overload. In conclusion, our study demonstrates the existence of a direct crosstalk between mTORC2 and MST1 that is critical for cardiac cell survival and growth.